2018
DOI: 10.1371/journal.pntd.0006362
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac findings in infants with in utero exposure to Zika virus- a cross sectional study

Abstract: BackgroundAntenatal exposure to Zika virus (ZIKV) is related to severe neurological manifestations. A previous study in Brazil reported an increased incidence of non-severe congenital heart defects in infants with diagnosis of congenital Zika syndrome but without laboratory confirmation of ZIKV infection in the mother or infant. The objective of this study is to report echocardiographic (ECHO) findings in infants with laboratory confirmed antenatal exposure to ZIKV.MethodologyCross sectional study of cardiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 19 publications
2
48
1
4
Order By: Relevance
“…In our study, only one child with ZIKV microcephaly had cardiac abnormalities, a much lower frequency than in the study by Orofino et al 9 . However, this data suggests that the importance given to the research of cardiac comorbidities in patients with ZIKV should be lower than other comorbidities, such as neurological ones.…”
Section: Discussioncontrasting
confidence: 85%
“…In our study, only one child with ZIKV microcephaly had cardiac abnormalities, a much lower frequency than in the study by Orofino et al 9 . However, this data suggests that the importance given to the research of cardiac comorbidities in patients with ZIKV should be lower than other comorbidities, such as neurological ones.…”
Section: Discussioncontrasting
confidence: 85%
“…This finding was important not only for the care of infants since rapid identification of this complication can lead to better medical care, but it also provided evidence of involvement of the peripheral nervous system in some infants with congenital Zika virus infection. At least two studies have reported an increased frequency of congenital heart defects among children with prenatal Zika virus exposure (Cavalcanti et al, 2017;Orofino et al, 2018). However, given that these defects have been mild in nature (e.g., secundum atrial and muscular ventricular septal defects), screening for these defects among Zika-exposed infants is not recommended.…”
Section: Zika Virus and Birth Defectsmentioning
confidence: 99%
“…[6][7][8] Although ZIKV seems to be prominently neurotropic, there are some reports of involvement of other organs, particularly the heart. Cavalcanti 10 None of the defects were severe.…”
Section: Introductionmentioning
confidence: 95%